Leadership matters : confronting the hard choices facing higher education - King, W. Joseph; Mitchell, Brian Christopher, 1953- (Johns Hopkins University Press, 2022)
"The authors explain what colleges must do-and must not do-to remain relevant in the coming decades. The authors begin from a premise that colleges and universities must evolve and adapt by modernizing their practices, monetizing their assets, focusing on core educational strategies, and linking explicitly to the modern world"--